(2-1,1-Bis(hydroxy-meth-yl)-2-oxidoeth-ylimino-meth-yl-4-chloro-phenolato-kap paN,O,O')dibutyl-tin(IV) - Reisi, R.; Misran, Misni; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The Schiff base ligand in the title compound, Sn(C4H 9)2(C11H12ClNO4), chelates to the Sn atom through the two deprotonated O atoms, as well as through the N atom, to confer an overall cis-C2SnNO2 trigonal-bipyramidal geometry at tin C - Sn - C = 130.3 (1)Â°. The hydr-oxy groups engage in O - Hâ¯O hydrogen bonding with the O atoms of adjacent mol-ecules, generating a chain running along the c axis.